(untitled) (Indonesian Tourism Justice Review, 2024)
Tourism in Indonesia often highlights the country’s rich cultural diversity, but it also poses risks to the preservation of indigenous languages and traditions. This paper examines how tourism development impacts the linguistic and cultural practices of indigenous communities, with particular focus on regions such as Bali, Papua, and Flores. Through interviews with indigenous leaders, cultural experts, and tourism operators, the study identifies the pressures tourism places on traditional languages and cultural practices, including their commercialization and marginalization. The paper explores the role of tourism in both protecting and undermining indigenous identities, and how cultural commodification contributes to the erosion of traditional values. Drawing from cultural preservation theories and case studies, the paper discusses strategies to safeguard indigenous languages and practices, including the implementation of cultural heritage policies, educational programs, and community-led tourism initiatives that prioritize cultural sustainability. The study concludes by recommending policies that integrate indigenous rights into tourism development planning and promote cultural sensitivity among tourists and tourism businesses.